2002
DOI: 10.1063/1.1483853
|View full text |Cite
|
Sign up to set email alerts
|

New analytical (2A′,4A′) surfaces and theoretical rate constants for the N(4S)+O2 reaction

Abstract: We report two new analytical fits of the ground potential energy surface ͑PES͒ ( 2 AЈ) and the first excited PES ( 4 AЈ) involved into the title reaction and its reverse, using ab initio electronic structure calculations from Papers I and II along with new grids of ab initio points by means of the second-order perturbation theory on CASSCF wave function ͓CASPT2 ͑17,12͒ G2/aug-cc-pVTZ͔ reported here ͑1250 points for the 2 AЈ PES and 910 points for the 4 AЈ PES͒. Some experimental data were also introduced to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(121 citation statements)
references
References 34 publications
12
109
0
Order By: Relevance
“…These two PESs have been accurately calculated by the same group of Barcelona University [31,32] who calculated the two PESs of reaction (10.b), so the analytical expression of these 2 A 0 and 4 A 0 PESs [33] is chosen in the present study. The rates of reaction (11) are obtained by a weighted sum in the following way:…”
Section: Potential Energy Surfaces and Vibrational Energies In The Nomentioning
confidence: 99%
“…These two PESs have been accurately calculated by the same group of Barcelona University [31,32] who calculated the two PESs of reaction (10.b), so the analytical expression of these 2 A 0 and 4 A 0 PESs [33] is chosen in the present study. The rates of reaction (11) are obtained by a weighted sum in the following way:…”
Section: Potential Energy Surfaces and Vibrational Energies In The Nomentioning
confidence: 99%
“…Tentatively, one could think of rationalizing the above differences from the results of Sharma and Duff [8] by correlating the final rotational temperature with the NO 2 well depth, since deep minima are expected to enhance randomization of the various degrees of freedom and eventually lead to formation of thermalized products. In fact, the MBE PES of Sayós et al [13] for the A state has a potential well slightly deeper than the DMBE one, which could conceivably explain the fact of the associated rotational distribution at T = 750 K lying closer to 750 K than the DMBE prediction itself. Thus, one could to some extent attribute the differences between our prediction and the one of Sharma and Duff [8] to the shallower minima of the LEPS forms.…”
Section: Resultsmentioning
confidence: 91%
“…For example Sayós et al have reported a series of studies [13,14] for different states of the NO 2 system, focusing mainly on the study of N + O 2 collision, whereas Ivanov et al [15] studied exchange and recombination on the O( 3 P ) + NO( 2 ) reaction with a newly fitted potential function. Although there is a vast literature on the NO 2 system (a complete review is out of the scope of this work), the specificity of the energy transfer of the title transition makes it a subject not so extensively explored.…”
Section: Introductionmentioning
confidence: 98%
“…The rate constant of reaction (3.33) was established with rather high accuracy, and measurements of different researchers are in good consistency with each other [62]. this reaction, conducted in [63,64], it was established that the activation barrier of reaction (3.33) was about 3000 K.…”
Section: (C) Ch 4 − O 2 Systemmentioning
confidence: 96%